Civil Society Organization Management Influencing to The Effectiveness for Strongness of Families - Inthawong ืNarawadee (Journal of Social Development and Management Strategy, 2021)
The purposes of this research were to study: 1) organization management; 2) internal environment and external environment of organization affecting organization management; and 3) effective of operation of Surin Provincial Healthy Family Institution. This was a qualitative research. The data was compiled from in-depth interview and participant observation was used with 15 key informants including personnel in Surin Provincial Healthy Family Institution, family members participating in the activities and networks related to operation. The results reveal that 1) Organization management, it is focusing on the working committee to meet, talk, and exchange working guideline. They utilize abilities of working committee to determine goals, organize and allocate resources of the organization through organization management process comprising planning, organization management, personnel allocation, coordination, control and develop “curriculum” to drive family tasks to success and achieve needs efficiently that the target group learns and changes their behaviors to build healthy family. 2) Environment affecting organization management, it is proved that management organization it has relationship with internal and external environment. The internal environment affecting the organization management includes vision, organization objectives, organization structure and leader. Meanwhile, the external environment affecting organization management consisted of public policy, network and community environment. 3) The operation efficiency, the results show that has constructive efficiency as it integrates and connects with all sectors including public sector, private sector and networks, as a result, the activities conducted by Surin Provincial Healthy Family Institution accommodating learning within family and supporting healthy family in Surin Province. In a nutshell, suggestions for Surin Provincial Healthy Family Institution are that they should develop younger generation to have knowledge, ability, strong will and volunteer mind as they can work together with the organization and continue the tasks of the organization for building healthy family through participating learning process.